2018
DOI: 10.1002/jper.17-0087
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminus of the amelogenin peptide influences the proliferation of human bone marrow mesenchymal stem cells

Abstract: A C-terminal amelogenin variant increased the proliferation of MSCs via an interaction with LAMP1 and the MAPK-ERK signaling pathway, indicating the possibility of using MSCs for tissue regeneration in the craniofacial region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Amelogenins are crucial components of developing extracellular enamel matrix, which direct the organization and mineralization of enamel. Studies have demonstrated that C-terminus of amelogenins induces division, differentiation, and maturation of MSCs, especially in cementoblastic lineage cells (Kunimatsu et al, 2017(Kunimatsu et al, , 2018. Additionally, cementoblastic differentiation of mesenchymal progenitor cells is tightly maintained by an autocrine system mediated by parathyroid hormone (PTH)related peptide (PTHrP) and the PTH/PTHrP receptor, thereby preventing DMSCs from premature differentiation into cementoblasts (Takahashi et al, 2019).…”
Section: Cementogenesismentioning
confidence: 99%
“…Amelogenins are crucial components of developing extracellular enamel matrix, which direct the organization and mineralization of enamel. Studies have demonstrated that C-terminus of amelogenins induces division, differentiation, and maturation of MSCs, especially in cementoblastic lineage cells (Kunimatsu et al, 2017(Kunimatsu et al, , 2018. Additionally, cementoblastic differentiation of mesenchymal progenitor cells is tightly maintained by an autocrine system mediated by parathyroid hormone (PTH)related peptide (PTHrP) and the PTH/PTHrP receptor, thereby preventing DMSCs from premature differentiation into cementoblasts (Takahashi et al, 2019).…”
Section: Cementogenesismentioning
confidence: 99%
“…The selection sequence consisted of the evaluation of the title (2873 articles), of the abstract (774 articles), and subsequently of the complete text (24 articles) (Figure 1). Of the latter, 10 [24][25][26][27][28][29][30][31][32][33] were excluded due to the descriptive analysis (Table 1), while 14 studies met the inclusion criteria (Table 2). In the 14 studies selected [8,[34][35][36][37][38][39][40][41][42][43][44][45][46], it was not possible to perform a quantitative analysis due to major differences in terms of the cell model, peptide concentrations, time points, and methodologies employed (Table 2).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…A recent in vitro study suggested that bone marrow MSC proliferation was increased in the presence of C-terminal of amelogenin and inhibited by anti-LAMP1 antibody or U0126. Increased phosphorylated ERK1/2 was observed in the presence of C-terminal of amelogenin, and decreased phosphorylated ERK1/2 was seen in the presence of anti-LAMP1 antibody or U0126 [39]. Recently it has been demonstrated that human recombinant amelogenin remarkably enhanced LAMP-1 staining in mouse cementblasts [40].…”
Section: Discussionmentioning
confidence: 98%